The Interplay Between Viral Infection and Cell Death: A Ping-Pong Effect - Alireza Nourazarian; Hadi Yousefi; Cigir Biray Avci; Behrouz Shademan; Emad Behboudi (Advances in Virology)
Programmed cell death (PCD) is a well-studied cellular mechanism that plays a critical role in immune responses, developmental processes, and the maintenance of tissue homeostasis. However, viruses have developed diverse strategies to bypass or manipulate the host apoptotic machinery to enhance their replication and survival. As a result, the interaction between PCD pathways and viruses has garnered increased interest, leading to many studies being published in recent years. This study aims to provide an overview of the current understanding of PCD pathways and their significance in viral infections. We will discuss various forms of cell death pathways, including apoptosis, autophagy, necroptosis, and pyroptosis, as well as their corresponding molecular mechanisms. In addition, we will show how viruses manipulate host PCD pathways to prevent or delay cell death or facilitate viral replication. This study emphasizes the importance of investigating the mechanisms by which viruses control the host’s PCD machinery to gain insight into the evolutionary dynamics of host-pathogen interactions and to develop new approaches for predicting and managing viral threats. Overall, we aimed to highlight new research areas in PCD and viruses, including introduction of new targets for the development of new antiviral drugs to modulate the cellular apoptotic machinery and novel inhibitors of host cell death pathways.